EVALUASI PENGEMBANGAN KAWASAN AGROPOLITAN PETERNAKAN AYAM PETELUR DI KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA - Rota Lana Misla; Ahyuni Ahyuni (JURUSAN GEOGRAFI FIS UNP, 2020)
The agropolitan area development program is building agricultural-based economic activities in the agribusiness area. This research of aims are know: 1) The development of the agropolitan area in Mungka District in 2012 and 2018 in terms of the number of breeders and the number of laying hens population. 2) Agribusiness system of Mungka agropolitan area in 2019. 3) Spatial system formed in Mungka agropolitan area based on evaluation of the area. This research method is quantitative with a spatial approach starting from the identification of the area to be examined through a location map to determine the factors that influence the agropolitan area. The results of the study of population and breeders of laying hens have increased and decreased in several years. For the supply of laying hens, almost all feed is purchased outside the agropolitan area. In general the business scale is 0 to 500 and the scale of business is 600 to 1,000, buying raw materials at kiosks in the agropolitan area. Chicken egg marketing covers the provinces of West Sumatra, Riau and Jambi. The spatial system formed in the Mungka agropolitan area is that the new Mungka District is capable as a production location but has not been able to provide its own raw materials so that it is purchased outside the agropolitan area, the spatial system of the agropolitan area formed in Mungka District is not in accordance with the ideal concept.